2020
DOI: 10.1029/2019wr026707
|View full text |Cite
|
Sign up to set email alerts
|

Water Table Depth and Soil Salinization: From Pore‐Scale Processes to Field‐Scale Responses

Abstract: The accumulation of salts in soils adversely influences plant growth and biological activity resulting in loss of yields and soil ecosystem services. Water table depth plays an important role on solute distribution through the unsaturated zone. We focus on the relationship between saline water evaporation from soil surfaces and water table depths. When the water table was hydraulically connected to the surface, we found more evaporatively driven sodium chloride precipitation at the surface with deeper water ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 46 publications
2
42
1
Order By: Relevance
“…We selected the predictors based on the relevance to soil salinization processes as follows: surface evaporation, plant transpiration, fertilizers, poor drainage, and a rising water-table depth ( 15 , 66 , 67 ). In addition, the interactions of five main factors influencing soil formation processes, comprising climate, topography, living organisms, parent material, and hydrologic dynamics, were considered ( 59 , 63 ).…”
Section: Methodsmentioning
confidence: 99%
“…We selected the predictors based on the relevance to soil salinization processes as follows: surface evaporation, plant transpiration, fertilizers, poor drainage, and a rising water-table depth ( 15 , 66 , 67 ). In addition, the interactions of five main factors influencing soil formation processes, comprising climate, topography, living organisms, parent material, and hydrologic dynamics, were considered ( 59 , 63 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies described contrasting results, whereby evaporation did not decrease when salt precipitation occurred, at least when the hydraulic connection between the salt crust and water table was maintained or the salt crust remained wet (Eloukabi et al, 2011(Eloukabi et al, , 2013Sghaier & Prat, 2009;Shokri-Kuehni, Norouzi Rad, et al, 2017;Veran-Tissoires et al, 2012). Recently, Shokri-Kuehni et al (2020) reported a relationship between the saline water evaporation rate in soil and water table depth. A laboratory experiment combined with infrared thermography further confirmed that water transport through the salt crust was possible if the water table was hydraulically connected to the surface and that this phenomenon prevented reduction in the evaporation rate despite the presence of the salt crust.…”
Section: And Shimentioning
confidence: 99%
“…Vadose Zone Journal Shokri-Kuehni, Vetter, et al, 2017), and CO 2 sequestration (Ott et al, 2014); it also accelerates rock weathering processes (Rodriguez-Navarro & Doehne, 1999). However, the dynamics of salt precipitation and evaporation processes are poorly understood because salt precipitation rates, fractions of soil surface covered by salt precipitation (hereafter cover fraction), and evaporation processes are controlled by complex interactions between the texture of soils, ambient conditions, water table depth, and types of saline solution (Eloukabi et al, 2013;Nachshon, Shahraeeni, et al, 2011;Norouzi Rad & Shokri, 2012;Shokri-Kuehni, Norouzi Rad, et al, 2017;Shokri-Kuehni et al, 2020). Saline water evaporation causes salt accumulation and precipitation on the soil surface, which in turn leads to evolution of the soil pore structure (Jambhekar et al, 2015).…”
Section: And Shimentioning
confidence: 99%
See 1 more Smart Citation
“…For flow around obstacles and interfacial forms, the effects of shading and direct radiation would affect the evaporation rate around these forms, as well as contribute to the flow dynamics via thermal buoyancy and altered flow parameters. In addition to this, enhancements to the porous media model would also allow for the simulation of related environmental problems such as subsurface gas migration or evaporation driven salt precipitation, as an expansion to the work described in Shokri-Kuehni et al (2020). Modifications to this model including multi-component gas transport or mineralization could be performed to allow for this.…”
Section: Discussionmentioning
confidence: 99%